Le Seigneur de la charité : une image de Charles Le Brun pour les Filles de la Charité - Alexandra Woolley (Bulletin du Centre de Recherche du Château de Versailles, 2006)
During the 1630s Vincent de Paul promised Louise de Marillac that he “would send for the painter” who would create a pious image for the Daughters of Charity. The print, titled The Lord of Charity, was drawn by Charles Le Brun, engraved by Pierre Daret and printed in 1640 by Antoine Hérault, who was close to the noble women of the Vincentian congregation. It represents Christ standing on a cloud on which is inscribed “For Christ’s love compels us. Cor. 2, 5”. His presence is protecting the Daughters of Charity, who are placed in the background, tending to the sick in a hospital. Widely disseminated within the community and copied on many occasions by its members, the engraving was designed to spiritually educate the “country girls” who had committed themselves to Vincent de Paul as “servants of the poor”.